2013
DOI: 10.1111/j.1435-5957.2012.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial quality and regional development: Characterizing SME sectors in low income areas

Abstract: This paper analyses the characteristics of SMEs in less‐developed areas in comparison with more advanced economies. The conceptual framework includes different factors making up the so‐called ‘entrepreneurial quality’ of the SME sector: the personal characteristics of the entrepreneurs (motivations and previous experience), different dimensions of the SMEs’ entrepreneurial orientation, and the patterns of the SMEs’ insertion in national and global value chains. The empirical analysis uses data of SMEs in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 42 publications
2
30
1
3
Order By: Relevance
“…As Fernández-Serrano and Romero (2012) note, the phenomenon of entrepreneurship is of particular interest when governments realize that the state alone is unable to ensure adequate levels of production and employment, thereby resulting in high unemployment, and this explains why the topic of self-employment is so important for Europe. In the same vein, authors such as Feather (1992), Klyver et al (2013) or Shapiro (2014) have found a certain relationship between the degree of unemployment and the growth rate of self-employment, which implies that the latter increases when salary-based employment opportunities are limited.…”
Section: Introductionmentioning
confidence: 99%
“…As Fernández-Serrano and Romero (2012) note, the phenomenon of entrepreneurship is of particular interest when governments realize that the state alone is unable to ensure adequate levels of production and employment, thereby resulting in high unemployment, and this explains why the topic of self-employment is so important for Europe. In the same vein, authors such as Feather (1992), Klyver et al (2013) or Shapiro (2014) have found a certain relationship between the degree of unemployment and the growth rate of self-employment, which implies that the latter increases when salary-based employment opportunities are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found a relationship between the entrepreneur's attitudes (such as proactivity or risk taking) and business results (Choe et al, 2013;Garavan et al, 2016;Fernández-Serrano and Romero, 2013). Nevertheless, the effect of entrepreneurial attitudes, as a component of IC, on innovation has not been directly addressed.…”
Section: Entrepreneurial Attitude and Innovation In Small Businessesmentioning
confidence: 99%
“…A su vez, a nivel mesoeconómico, la calidad de los emprendedores/empresarios condiciona las características de las empresas en un ámbito territorial determinado, es decir, la calidad del tejido empresarial (Romero, 2011;Fernández-Serrano y Romero, 2013). Ésta, por su parte, viene definida por una serie de factores que inciden en la capacidad de las empresas para impulsar el crecimiento y el desarrollo económicos en un territorio.…”
Section: Estado De La Cuestión Y Marco Teóricounclassified